Two new species and a new record of mealybugs (Hemiptera, Coccoidea, Pseudococcidae) from Iran - Moghaddam, Masumeh (Zootaxa, 2010)
Chorizococcus mirzayansi Moghaddam sp. n. and Phenacoccus betae Moghaddam sp. n. are described and illustrated in detail based on adult females from Iran. The species C. mirzayansi was collected on the leaves of Opuntia ficus-indica (Cactaceae) and P. betae was collected on the roots of Beta vulgaris (Betulaceae). The mealybug Phenacoccus perillustris Borchsenius is recorded from Iran for the first time. A key and a checklist are provided for the six species of Phenacoccus known from Iran.